Probiotics for Preventing Ventilator-Associated Pneumonia in Mechanically Ventilated Patients: A Meta-Analysis with Trial Sequential Analysis - Weng, Hong; Li, Jian-Guo; Mao, Zhi; Feng, Ying; Wang, Chao-Yang; Ren, Xue-Qun; Zeng, Xian-Tao (Frontiers in Pharmacology, 2017)
Background and Objective: Ventilator-associated pneumonia (VAP) is still an important cause of morbidity and mortality in mechanically ventilated patients. The efficacy of the probiotics for preventing VAP is still controversial. Present study was conducted to comprehensively evaluate the effect of probiotics on VAP prevention in mechanically ventilated patients. Methods: PubMed, Embase, and CENTRAL were searched up to September 2016. Eligible trials designed with randomised controlled trials (RCTs) comparing probiotics with control in mechanically ventilated patients were included. Risk ratios (RRs) and mean differences (MDs) with 95% confidence intervals (CIs) were estimated with fixed or random effects models. Trial sequential analysis (TSA) was performed using TSA 0.9beta software. Results: Thirteen RCTs (N = 1969) were included. Overall, probiotics were associated with reduced incidence of VAP (RR = 0.73, 95% CI = 0.60 to 0.89; P = 0.002), which was confirmed by TSA (TSA adjusted 95% CI = 0.55 to 0.96). However, no significant difference was observed in 90-day mortality (RR = 1.00, 95% CI = 0.72 to 1.37; P = 0.99), overall mortality (RR = 0.84, 95% CI = 0.70 to 1.02; P = 0.09), 28-day mortality (RR = 1.06, 95% CI = 0.72 to 1.57; P = 0.99), intensive care unit (ICU) mortality (RR = 0.97, 95% CI = 0.74 to 1.27; P = 0.82), hospital mortality (RR = 0.81, 95% CI = 0.65 to 1.02; P = 0.07), diarrhea (RR = 0.99, 95% CI = 0.83 to 1.19; P = 0.92), length of ICU stay (MD = -2.40 days, 95% CI = -6.75 to 1.95; P = 0.28), length of hospital stay (MD = -1.34 days, 95% CI = -6.21 to 3.54; P = 0.59), and duration of mechanical ventilation (MD = -3.32 days, 95% CI = -6.74 to 0.09; P = 0.06). Conclusions: In this meta-analysis, we found that probiotics could reduce the incidence of VAP in mechanically ventilated patients. It seems likely that probiotics provide clinical benefits for mechanically ventilated patients.